Benedetto Varchi and Art Theory of the Cinquecento - Alyoshin, Pavel А. (Actual Problems of Theory and History of Art, 2013)
In this article we are discussing principal propositions of Benedetto Varchi’s Art Th eory in the context of the whole Art Th eory of the Cinquecento. Special attention is given to Varchi’s refl ection about the correlation between visual arts and literature.
Keywords: Renaissance art; Cinquecento; art theory; Benedetto Varchi; Michelangelo